Efficiency of the Regional Revenue Agency's Services (Case Study at the Supiori Regency Taxpayer Supiority Service Number) - Sri Handayani (Budapest International Research and Critics University, 2021)
The efficacy of services has been established as the foundation for imaging for individuals in need of services. The link between the elements affecting palayanan's efficacy and the outcomes of public satisfaction has been shown adequately in earlier research. The objective of this study was to examine the Taxpayer Identification Number of Development Planning Agency at Sub-National Level of Supori Regency service quality in terms of elements that might impact service quality. The findings of this study suggest that the community is dissatisfied with the service provided by the Supiori Regency Taxpayer Identification Number, necessitating the implementation of different repair processes by both the head and workers. Additionally, the findings of this study support the need for additional research to demonstrate how efforts to oversee and assess human resources, service management, and infrastructure may result in future increases in community satisfaction with services in the Development Planning Agency at Sub-National Level Supiori Regency. The solution to the constraints encountered during the efficiency process at the Supiori Regency Development Planning Agency at Sub-National Level office is as follows: (a) the need to improve employee education with a high school diploma or equivalent to a Bachelor (S1) level of competence; (b) a focus on quick and uncomplicated services for the sake of community satisfaction; and (c) procurement of cutting-edge computer facilities.